2020
DOI: 10.1002/osp4.408
|View full text |Cite
|
Sign up to set email alerts
|

Exercise plus caloric restriction lowers soluble RAGE in adults with chronic kidney disease

Abstract: Introduction: The incidence of chronic kidney disease (CKD) has increased in recent years. CKD is associated with obesity, type 2 diabetes, and cardiovascular disease, although the mechanism remains unclear. Elevated soluble form of the receptor for advanced glycation end products ( RAGE) is related to proinflammatory signaling pathways that may promote diabetic nephropathy and vascular dysfunction. Because lifestyle modification reduces systematic inflammation in adults with obesity and hyperglycaemia, the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Such responses include AMPK activation, autophagy, ROS elimination, Nrf2 signaling pathway activation and enhancement of antioxidative capacity in the kidney [ 231 , 232 , 233 , 234 , 235 ]. In certain studies, exercise has been shown to have a synergistic effect on CR [ 236 , 237 ]. Therefore, CR and exercise may be applied simultaneously to enhance kidney function in diabetes [ 238 , 239 ].…”
Section: Therapeutic Approaches To Counteracting Dkdmentioning
confidence: 99%
“…Such responses include AMPK activation, autophagy, ROS elimination, Nrf2 signaling pathway activation and enhancement of antioxidative capacity in the kidney [ 231 , 232 , 233 , 234 , 235 ]. In certain studies, exercise has been shown to have a synergistic effect on CR [ 236 , 237 ]. Therefore, CR and exercise may be applied simultaneously to enhance kidney function in diabetes [ 238 , 239 ].…”
Section: Therapeutic Approaches To Counteracting Dkdmentioning
confidence: 99%
“…In interventional models, training was indeed shown to efficiently decrease AGEs in obese-diabetic rodents [164,167]. Similarly, in humans, the practice of regular exercise was demonstrated to be effective in lowering AGEs levels in chronic inflammation [166] and soluble RAGEs in obese-dysglycemic patients [165] .…”
Section: Exercise Can Control the Formation Of Advanced Glycation End-productsmentioning
confidence: 95%
“…Exercise, by activating muscle glucose uptake, contributes to glucose balance and to enhance glycemic control in humans [163], blunting the formation of AGEs. The higher energy requirement, in trained organisms, diminishes the availability of glycating intermediates deriving from glycolytic (glucose-6-phosphate; fructose-6phosphate) and polyol (fructose-3-phosphate; 3-deoxyglucosone) pathways [13,164,165]. Higher levels of Inflammation and the activation of immune cells represent a potential trigger for the increase in oxidative stress.…”
Section: Exercise Can Control the Formation Of Advanced Glycation End-productsmentioning
confidence: 99%
“…The increased uptake and oxidation of circulating FFAs during exercise also contribute to reduce muscle and liver inflammation, and insulin resistance [35]. Lastly, regular exercise was shown to efficiently decrease AGEs in obese-diabetic animal models [68,79] and in humans [80]. AGEs production is mainly triggered by hyperglycemia and oxidative stress, and contributes to increase organ-specific and systemic inflammation [81].…”
Section: Exercise Modulates Metabolic Status and Inflammationmentioning
confidence: 99%